(3CTcGd GdhSGFW aj GdefMQaGJ hGdHSGFWs - (3MSf Hf Ndjd Hf eRQhY, CHh eMeO, TeS GdOjf GdWHfj GdcQGOjSj,J (B887 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3ajbhd eDda gPG GdcJGH Efi deG QCjJ HYV GdBdGJ jJhUd Hg Edi eYQag GdChbGJ Gdfi HgG jMaX MOhO GdYHGOGJ s
(3BNQgG (B:s
(3cd OGFQI ai GdhLg GdLfhHi Cbd ef fUa OGFQI hai GdTeGd GcKQ hbYg ehGRjkG deYOd GdfgGQ hGddg CYde s
(3Gdajde ZjQ ehLhOs
(3ajgG QShe gfOSjI hLOGhd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B189 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B223s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B129 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B9 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs